Constituent aspects of workplace guidance in secondary VET. Issue 5 (1st June 2015) - Swager, Robert; Klarus, Ruud; van Merriënboer, Jeroen J. G.; Nieuwenhuis, Loek F.M.
Abstract : Purpose: – This paper aims to present an integrated model of workplace guidance to enhance awareness of what constitutes good guidance, to improve workplace guidance practices in vocational education and training. Design/methodology/approach: – To identify constituent aspects of workplace guidance, a systematic search of Web of Science was conducted, focussing on mentoring literature, research on institutional socialization tactics and research on didactical interventions and their effects. Findings: – The model interprets workplace learning as a relational and integrated process of participation, acquisition, guidance and social interaction. Psychosocial support, structure-providing interventions and didactical interventions are discussed as essential components of guidance. How these components are enacted is influenced by the characteristics of training firms and their employees' readiness to provide guidance. This makes guidance an intrapersonal process. Workplace guidance is also an interpersonal process in which the agencies of employees mediate the relationship between guidance and interaction, and the agencies of trainees mediate the relationship between, on the one hand, participation and acquisition and, on the other hand, social interaction. Originality/value: – Integrated models of what constitutes good workplace guidance are rare. To fill this gap, this paper highlights constituent aspects of workplace guidance and brings them together in an integrated model. The model can help mentors/employees choose effective interventions to improve workplace learning.